Preoperative assessment of breast cancer: Multireader comparison of contrast-enhanced MRI versus the combination of unenhanced MRI and digital breast tomosynthesis. (February 2020) - Girometti, Rossano; Marconi, Valentina; Linda, Anna; Di Mico, Luisa; Bondini, Federica; Zuiani, Chiara; Sardanelli, Francesco
Abstract: Purpose: To compare the sensitivity for breast cancer (BC) and BC size estimation of preoperative contrast-enhanced magnetic resonance imaging (CEMRI) versus combined unenhanced magnetic resonance imaging (UMRI) and digital breast tomosynthesis (DBT). Patients and methods: We retrospectively included 56 women who underwent DBT and preoperative 1.5 T CEMRI between January 2016–February 2017. Three readers with 2–10 years of experience in CEMRI and DBT, blinded to pathology, independently reviewed CEMRI (diffusion-weighted imaging [DWI], T2-weighted imaging, pre- and post-contrast T1-weighted imaging) and a combination of UMRI (DWI and pre-contrast T1-weighted imaging) and DBT. We calculated per-lesion sensitivity of CEMRI and UMRI + DBT, and the agreement between CEMRI, UMRI and DBT versus pathology in assessing cancer size (Bland-Altman analysis). Logistic regression was performed to assess features predictive of cancer missing. Results: We included 70 lesions (64% invasive BC, 36% ductal carcinoma in situ or invasive BC with in situ component). UMRI + DBT showed lower sensitivity (86–89%) than CEMRI (94–100%), with a significant difference for the most experienced reader only ( p = 0.008). False-positives were fewer with UMRI + DBT (4–5) than with CEMRI (18–25), regardless of the reader ( p = 0.001–0.005). For lesion size, UMRI showed closer limits of agreement with pathology than CEMRI or DBT. Cancer size ≤1 cm was the only independent predictor for cancer missing for both imaging strategies (Odds ratio 8.62 for CEMRI and 19.16 for UMRI + DBT). Conclusions: UMRI + DBT showed comparable sensitivity and less false-positives than CEMRI in the preoperative assessment of BC. UMRI was the most accurate tool to assess cancer size. Highlights: Combined UMRI + DBT shows high sensitivity in the preoperative assessment of breast cancer. UMRI + DBT avoids most false-positives induced by CEMRI. In combined imaging, UMRI is the better predictor of cancer size at pathology. UMRI + DBT is a potential alternative to CEMRI in the preoperative assessment of breast cancer.